Associations between pornography exposure, body image and sexual body image: A systematic review - Paslakis, Georgios; Chiclana Actis, Carlos; Mestre-Bach, Gemma (SAGE Publications Ltd, 2022)
There is evidence for associations between pornography exposure and sexual behaviors of adults and adolescents. Here, we review associations between pornography exposure and body image/sexual body image. Using a systematic search, we found 26 studies meeting inclusion criteria. Compelling evidence shows that frequency of pornography exposure is associated with negatively perceived body image and sexual body image; both heterosexual men and women appear to be affected. Due to scarcity of studies in adolescents and non-heterosexual samples, findings cannot be generalized to adolescents or individuals who identify as sexual minorities. Implications and future directions are discussed. © The Author(s) 2020.
Keywords: body image; genital self-image; porn; pornography; sexual body image; Scopus; JCR